2021
DOI: 10.1186/s13567-021-00955-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of ergosterol peroxide in a pig model of porcine deltacoronavirus (PDCoV) infection involves modulation of apoptosis and tight junction in the small intestine

Abstract: Porcine deltacoronavirus (PDCoV) is a newly discovered swine enteropathogenic coronavirus with worldwide distribution. However, efficient strategies to prevent or treat the infection remain elusive. Our in vitro study revealed that ergosterol peroxide (EP) from the mushroom Cryptoporus volvatus has efficient anti-PDCoV properties. The aim of this study is to evaluate the potential of EP as a treatment for PDCoV in vivo and elucidate the possible mechanisms. Seven-day-old piglets were infected with PDCoV by ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
(44 reference statements)
1
25
0
Order By: Relevance
“…However, different levels of PDCoV RNA were detected in multiple organs by RT-PCR. Although the strain and dose of the virus, the age of pigs or the time of euthanasia varied in different studies, PDCoV RNA was usually detected in the duodenum, jejunum, ileum, cecum, colon, liver, spleen, kidney, lung and MLN ( 2 , 12 , 39 41 , 45 ), and the quantities are relatively high in the duodenum, jejunum, ileum, cecum and colon. Low to moderate quantities of viral RNA are occasionally detected in the rectum, stomach, diaphragm, heart, inguinal lymph node, tonsil and muscle from rear leg ( 41 , 45 ).…”
Section: Pathogenicity and Infection Dynamics Of Pdcovmentioning
confidence: 99%
See 3 more Smart Citations
“…However, different levels of PDCoV RNA were detected in multiple organs by RT-PCR. Although the strain and dose of the virus, the age of pigs or the time of euthanasia varied in different studies, PDCoV RNA was usually detected in the duodenum, jejunum, ileum, cecum, colon, liver, spleen, kidney, lung and MLN ( 2 , 12 , 39 41 , 45 ), and the quantities are relatively high in the duodenum, jejunum, ileum, cecum and colon. Low to moderate quantities of viral RNA are occasionally detected in the rectum, stomach, diaphragm, heart, inguinal lymph node, tonsil and muscle from rear leg ( 41 , 45 ).…”
Section: Pathogenicity and Infection Dynamics Of Pdcovmentioning
confidence: 99%
“…Recently, our in vitro study found that PDCoV activates p38 signaling pathway to favor its replication ( 64 ). Later, we employed piglet models and illustrated that phosphorylated p38 levels in jejunum and ileum of PDCoV-infected piglets upregulated ( 2 ). Jeon et al confirmed that JNK1/2 and p38 were involved in the replication of PDCoV by affecting viral biosynthesis and progeny release ( 65 ).…”
Section: Pathogenesis Of Pdcovmentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Editor, porcine Delta Coronavirus (PDCoV), is a virus of the corona family of porcine enteropathogenic virus that was recently discovered and has a global pandemic. Therefore, effective strategies to prevent or treat infection remain unattainable [1]. It should be noted that the delta virus can increase the risk of admission to the hospital [2] and it seems that the rate of hospitalization due to this infection is up to twice as much as the previous infection [2] and increasing the hospital admission rate increases the pressure on the already exhausted health system and can put pressure on it [3].…”
mentioning
confidence: 99%